Critical thinking of EAW students - Engku Ibrahim, Engku Haliza (2012)
Critical thinking skills is one of the essential life-long learning skill which has always been recognized as an essential element in tertiary education. Thus it is incumbent for educators to incorporate critical thinking skills at all levels. At the International Islamic University Malaysia, this skills is introduced in the English for Academic Writimg (EAW) class which is one of the university required courses for our students. The purpose is to enable them to be able to use the English language effectively in an academic setting that uses English as the medium of instruction. The course requires students to produce a mini research paper at the end of the semester. Being an Islamic institution, the students are required to be able to integrate the Islamic perspective in their writings. This paper investigates the extent to which Engineering and Human Science students are able to incorporate the Islamic perspective relevant to their respective disciplines. 26 scripts were analysed using Bloom’s critical thinking framework. The findings revealed that all students were able to incorporate Islamic perspectives though not all were able to apply the higher order thinking skills.